Developing Listening Materials Based on Bottom Up Strategy for Students of English Education - Armala Dita; Syaprizal Syaprizal; Agus Triyogo (EDULIA: English Education, Linguistic and Art Journal, 2020)
The purpose of this research is to develop listening material based on bottom up strategy that can make students master listening skills. This research method is the Research and Development (R&D) method. This method consists of identification of material needs, exploration of needs, realization of contextual materials, realization of pedagogical materials, production of materials, use of student materials and evaluation of materials against agreed goals. The population in this study were all students of the first semester English Education study program at STKIP-PGRI Lubuklinggau Academic Year 2020/2021. The results of this study make it easier for students to work on questions on the material that has been developed and make them more quickly understand. In conclusion, developing listening material based on a bottom-up strategy, researchers received a positive response from first semester students because it could help them learn to listen for general communication. In addition, researchers also use the bottom up strategy to develop this listening material, so that it can help make it easier for students to learn to listen for general communication. So, in this study the researchers succeeded in helping students facilitate listening learning in this first semester with a positive response from all students. Keywords: Bottom Up Strategy, Developing, Listening, Material